(untitled) (Bangladesh Pharmaceutical Journal, 2021)
Syzygium jambos L. belonging to the family Myrtaceae has a long history of using as a dietary fruit and folklore medicine. Investigation of this fruit was carried out to evaluate the different chemical properties and biological activities. The moisture and ash content of the fruit sample were calculated as 86.88 ± 0.61% and 0.29±0.02%, respectively. Dried powder of the fruit was extracted successively with nhexane, dichloromethane (DCM) and methanol (MeOH). UV-Visible and FT-IR spectral analyses confirmed the presence of unsaturated carboxylic acid in n-hexane, unsaturated ester in DCM and a diketone in MeOH extracts. Cytotoxicity assay of different extracts was carried out against HeLa and Vero cell lines and no extract was found to be cytotoxic. Total phenolic contents of the n-hexane, DCM and MeOH extracts were 15.39 ± 0.24, 31.32 ± 0.25 and 42.19 ± 0.16 mg gallic acid equivalent per gram of dry extract, respectively and total flavonoid content of n-hexane, DCM and MeOH extracts were 6.52 ± 0.18, 15.55 ± 0.16 and 8.36 ± 0.16 mg quercetin equivalent per gram of dry extract, respectively. This study establishes that S. jambos fruit can be a potential source of natural antioxidants. Bangladesh Pharmaceutical Journal 24(2): 111-116, 2021